The effects of transmission power control in mobile ad-hoc sensor networks - Mohamad Nazim, Jambli; Halikul, Lenando; Kartinah, Zen; Sinarwati, Mohamad Suhaili; Tully, Alan (Elsevier, 2012)
Preserving energy is a very critical issue in mobile ad-hoc sensor networks (MASNETs) because sensor nodes have a severe resource constraints due to their lack of processing power and limited in power supply. Since the communication is the most energy consuming activities in MASNETs, the power use for transmission or reception of packet should be managed as much as possible. One way to reduce energy consumption is by applying transmission power control (TPC) technique to adjust the transmission power in communication between nodes. This technique has been widely studied in MASNETs. However, as MASNET applications emerge, the unique characteristics of this network such as severe resource constraints and frequent topology change suggest that TPC might be useful to reduce energy consumption in MASNETs. Therefore, we investigate different effects of TPC on Ad hoc On-Demand Distance Vector (AODV) routing protocols for MASNETs. AODV is used as a medium of communication to assist the investigation of the effects of TPC in multihop communication in this networks with RandomWay Point (RWP) mobility model. Our simulation results show a noticeable effects of TPC implementation technique on MASNETs in respect to transmission energy consumption and packet received ratio at low node mobility. These results support the use of TPC technique to enhance the performance of multihop AODV routing protocol in MASNETs.